On the geology of Cape Seal, Biton-Keurbooms estuary and environs, with a description of a Fenestellid genus of Hemitrypa from Drooge rivier, Plettenbergs Bay - Rossouw, P. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1932.